Diagnostic accuracy and safety of renal tumour biopsy in patients with small renal masses and its impact on treatment decisions - Bassam Mazin Hashim; Abbas Chabok; Börje Ljungberg; Erland Östberg; Farhood Alamdari (Scandinavian Journal of Urology)
Objective: To assess the safety and diagnostic accuracy of renal tumour biopsy (RTB) in patients with small renal masses (SRM) and to assess if RTB prevents overtreatment in patients with benign SRM.